2019
DOI: 10.4078/jrd.2019.26.1.12
|View full text |Cite
|
Sign up to set email alerts
|

Smoking as a Preventable Risk Factor for Rheumatoid Arthritis: Rationale for Smoking Cessation Treatment in Patients with Rheumatoid Arthritis

Abstract: Rheumatoid arthritis (RA) is a chronic inflammatory disease of multifactorial etiology. Smoking is considered one of the most established environmental risk factors for RA development and severity. A large proportion of patients with RA have a high prevalence of smoking history. Previous studies have provided evidence suggesting that smoking is associated with the development of RA. Smoking has been associated with several pathogenic mechanisms on RA development such as oxidative stress, inflammation, and epig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…According to research in Israel avoiding offending diet and intake of proper diet may affect the flares of PR. Smoking can also trigger the process of Citrullination by affecting the immune reactions of the HLA Gene [39]. Most of the case study reports that the onset of PR frequently begins in the late afternoon and early morning [40,41].…”
Section: Environmental Factorsmentioning
confidence: 99%
“…According to research in Israel avoiding offending diet and intake of proper diet may affect the flares of PR. Smoking can also trigger the process of Citrullination by affecting the immune reactions of the HLA Gene [39]. Most of the case study reports that the onset of PR frequently begins in the late afternoon and early morning [40,41].…”
Section: Environmental Factorsmentioning
confidence: 99%
“…Physiopathologically, there is growing evidence that RA begins in the lung with active citrullination of vimentin peptides induced by tobacco exposure ( 2 , 3 ). Similarly, epidemiological data showed that in a global RA population, most of the patients were presenting a tobacco abuse history (former smokers or ex-smokers) ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, evidence suggest that half of the patients with RA are current smokers at the time of disease onset [ 11 ] and up to 26% continue to smoke despite the risk for increased RA complications, hospitalizations due to cardiovascular disease and respiratory tract infections, osteoporosis, and poor response to treatment [ 13 , 14 ]. Factors associated with smoking persistence in patients with RA are thought to be a combination of biological, psychological and social factors including managing RA pain, using smoking as a coping strategy, behavior carried from adolescence, and/or limited knowledge about the effects of smoking on the disease [ 15 ].…”
Section: Introductionmentioning
confidence: 99%